High-Resolution Melting Curve Analysis, a Rapid and Affordable Method for Mutation Analysis in Childhood Acute Myeloid Leukemia - Liu, Yin; Tang, Jingyan; Wakamatsu, Peter; Xue, Huiliang; Chen, Jing; Gaynon, Paul S.; Shen, Shuhong; Sun, Weili (Frontiers in Pediatrics, 2014)
Background: Molecular genetic alterations with prognostic significance have been described in childhood acute myeloid leukemia (AML). The aim of this study was to establish cost-effective techniques to detect mutations of FMS-like tyrosine kinase 3 (FLT3), Nucleophosmin 1 (NPM1), and a partial tandem duplication within the mixed lineage leukemia (MLL-PTD) genes in childhood AML. Procedure: Ninety-nine children with newly diagnosed AML were included in this study. We developed a fluoresent dye SYTO-82 based high resolution melting curve (HRM) anaylsis to detect FLT3 internal tandem duplication (FLT3-ITD), FLT3 tyrosine kinase domain (FLT3-TKD) and NPM1 mutations. MLL-PTD was screened by real-time quantitative PCR. Results: The HRM methodology correlated well with gold standard Sanger sequencing with less cost. Among the 99 patients studied, the FLT3-ITD mutation was associated with significantly worse event free survival (EFS). Patients with the NPM1 mutation had significantly better EFS and overall survival. However, HRM was not sensitive enough for minimal residual disease monitoring. Conclusions: HRM was a rapid and efficient method for screening of FLT3 and NPM1 gene mutations. It was both affordable and accurate, especially in resource underprivileged regions. Our results indicated that HRM could be a useful clinical tool for rapid and cost effective screening of the FLT3 and NPM1 mutations in AML patients.